Mobile Technologies in Education: Parents’ Preferences for Tools Supporting Children’s Development - Panasiuk-Kwiatek, Magdalena; Berlińska, Ewelina (Technologie mobilne w edukacji: preferencje rodziców dotyczące narzędzi wspierających rozwój dzieci, 2024)
Aim: The aim of the article is to analyse parents’ preferences regarding the use of mobile applications in children’s education and to identify the key features of applications that they consider most valuable. Methodology: The study was conducted using an online survey targeting parents of children in grades 1-8 (N = 121, pilot study), exploring their preferences for educational apps and mobile technology. Results: Over 60% of children use mobile devices every day mainly for entertainment purposes, less often for educational purposes. Parents point out the importance of applications that develop logical thinking, creativity and manual skills. Implications and recommendations: Mobile apps have the potential to support children’s development, provided they are tailored to their age and needs. Teachers’ and parents’ awareness of the effective use of these tools should also be raised. Originality/value: The survey provides unique data on parents’ preferences and perceptions of technology, which can help design more effective educational applications.
Business Informatics = Informatyka Ekonomiczna, 2024, Nr 1-2 (67-68), s. 64-74
Keywords: mobile technology; education and child development; educational apps; gamification; technologie mobilne; edukacja i rozwój dzieci; aplikacje edukacyjne; grywalizacja